Electric Feel. - Keeling, Kara (Cultural Studies, 2014)
Electric Feel: Transduction, Errantry and the Refrainassesses what certain logics gleaned from selected popular music songs might offer to ongoing efforts to renegotiate bonds, institutions and political possibilities shaped by the violences characteristic of capitalism, cisgender and white supremacy, neoliberal multiculturalism and contemporary geopolitics. Making Gilles Deleuze and Felix Guattari's concepts of ‘the Refrain’, and ‘music’ available as heuristics and technologies to contribute to ongoing explorations of the role that sound plays and yet might play in contemporary Euro-American feminist cultural studies, this essay is animated by what might be called, following Édouard Glissant, a mode of ‘scholarly errantry’. If feminism was music and feminists musicians, it could be said that feminism's histories, its preoccupations, its shifting and fluid subjects and debates, its styles, its canonical texts and concepts, are its refrains, the things to which it returns, its territory, the aspects of feminism that exert a force in the world. These have political indices as well as scholarly, creative ones. Insofar as academic feminism traverses disciplines and constitutes itself as such through reference to those narratives and intellectual lineages that it claims as its own, it has carved out a terrain, a ‘field’, and a set of constituents, but nonetheless contested, organizations and their stated priorities, interests and common senses. The present essay asks, what music might contemporary feminisms make when their existing refrains are placed under pressure? How might sound and music offer insightful support for generating and relating concepts to the rapidly changing present circumstances that queer anti-racist feminisms actively participate in shaping? What tales of errantry might such feminisms tell today?